Temperature, salinity and depth measurements from a moored CTD deployed in a glacier-fed fjord (Nuup Kangerlua, Greenland) between June and September 2019 - Beaton, Alexander; Hendry, Katharine R; Hatton, Jade Elizabeth; Meire, Lorenz (PANGAEA, 2025)
This is time-series temperature, salinity and depth data from a conductivity, temperature and depth (CTD) probe deployed in a glacier-fed fjord (Nuup Kangerlua) between 14th June and 13th September 2019. The instrument was anchored to a cliff via a wire and submerged at an average depth of 5 m. The instrument was recorded a measurement every 10 minutes. During a three-month monitoring period salinity varied between 14.19 and 30.81, temperature varied between 0.13 and 6.91 °C and depth varied between 2.27 and 7.87 m.